An investigation of the repairability of ferrocement - Adajar, Jose Caringal (1989)
Ferrocement is known to have an advantage over the building materials in that it can be repaired efficiently. One matter that is not quite clear, however, involves the question on how much of the original strength of a ferrocement element could be recovered after the repair. To address this, three types of loading were tested in the following experimental study. These were compression, tension, and flexure. For each type, the mixture of the constituent materials was varied into 1:2 45%, 1:2.5, 50% and 1.3 55% (cement : sand water cement ration by weight). for every mixture, the number of layers of wire mesh was also varied into two layers, 4 layers, and 5 layers. A total of one hundred and sixty-two ferrocement specimens were used in this investigation, with fifty-four each for compression, tension and flexure.
Each specimen was tested to its ultimate load, after it which was repaired and tested with the same material properties. The recovered strength was then compared with the original strength. The results of the study proved that a ferrocement element which has been subjected to failure can be repaired efficiently with a highly considerable strength recovery.
Typescript.
Thesis (M.S.)--University of the Philippines Diliman.
Keywords: Reinforced concrete